Kejadian Penyakit Infeksi Saluran Pernapasan Akut pada Pekerja Tambang Kapur - Akili, Rahayu Hasan; Kolibu, Febi; Tucunan, Ardainsyah C (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Limestone industrial has been polluting the air with dust and combustion gases of limestone. The main effects of limestone dust to worker that dust in the form of both acute lung disorder and chronic disruption of physiologic function, eye irritation, irritation of sensory as well as the accumulation of harmful substances in the body. The effect on the respiratory tract is the irritation of the respiratory tract (ISPA). One of the negative effects of the limestone processing activities is environmental degradation that marked the air pollution and the growing number of diseases related to the respiratory tract. in the Buliide Village on 2014 ISPA 348 cases, 185 cases of asthma, and pneumonia 10 cases. The purpose of this study is determine the factors related to the case of respiratory disease in limestone mining workers in Buliide Sub-District, Kota Barat District, Gorontalo province. Method: Type of research used in this research is observational research with cross sectional analytic study, which is a plan that examines the dynamics of the correlation or association between the independent variables (independent) and dependent variable (dependent) at the same time (Point Time Approad). The research was done at Buliide Village, Kota Baru District, Gorontalo Province in 2015. Result: The results showed that there is a relationship between working duration, age, smoking behavior, have a relation with case of respiratory disease. While working period do not have any relation with case of respiratory disease in limestone mining workers in Buliide Sub-District, Kota Barat District, Gorontalo province. Conclusion: It was advisable for the government to provide education on prevention and control of dust hazards, information dangers of smoking, and health check on where the service is available.